2014
DOI: 10.1021/jo5002164
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Thiochromenes via Intramolecular Tandem Thio-Michael Addition of in Situ Generated α,β-Unsaturated Aldehydes

Abstract: An efficient and highly stereoselective strategy for the synthesis of 2,3-substituted thiochromenes having a complex and easily transformable group at the stereogenic center has been developed via a tandem thio-Michael addition reaction of an in situ generated α,β-unsaturated aldehyde sugar derivative. The protocol is superior to reported protocols in that the carbohydrate-derived substituent at the stereogenic center of the thiochromene is versatile and is amenable for further transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…21,22 The search for the chloro-and fluorocyclization methodologies is interesting since the nature of halogen substituents is reported to affect the adsorption, metabolism, distribution, and excretion properties of bioactive molecules. 21 In continuation of our previous studies on the stereoselective synthesis of carbohydrate fusedthiochromans and thiochromenes, 23−25 We recently reported that treatment of sulfoxide 1 with NaOAc in acetic anhydride resulted in the formation of an unexpected fused aryl-S-glucoside 2, presumably via an unusual C → S rearrangement reaction as shown in Scheme 1, 25 and this provided the substrate for the benzothiophene synthesis in the current study.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…21,22 The search for the chloro-and fluorocyclization methodologies is interesting since the nature of halogen substituents is reported to affect the adsorption, metabolism, distribution, and excretion properties of bioactive molecules. 21 In continuation of our previous studies on the stereoselective synthesis of carbohydrate fusedthiochromans and thiochromenes, 23−25 We recently reported that treatment of sulfoxide 1 with NaOAc in acetic anhydride resulted in the formation of an unexpected fused aryl-S-glucoside 2, presumably via an unusual C → S rearrangement reaction as shown in Scheme 1, 25 and this provided the substrate for the benzothiophene synthesis in the current study.…”
supporting
confidence: 58%
“…31 Sulfoxides 1a−e and aryl-S-glycosides 2a−e were synthesized according to previously published protocols. 25 All reactions were monitored by thin layer chromatography (TLC) on aluminum-backed silica gel 60 F254 plates using an ascending technique. The plates were visualized by spraying with a 1:1 solution of 5% p-anisaldehyde in ethanol and 10% sulfuric acid in ethanol and then baking at 150 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The attractiveness of the protocol is its ability to Scheme 1. In continuation of our interest in the synthesis of organosulfur compounds, [31][32][33][34][35] we herein report a regio-and stereoselective three-component synthesis of novel (E)-1,3-diphenyl-1butene derivatives 7, that contain a sulfur atom, in the absence of a metal or a strong acid catalyst (Scheme 1b). …”
mentioning
confidence: 99%
“…For instance, Wacharasindhu et al exploited the environmental compatibility and readily availability of diacetoxy-iodobenzene (DIB) in the activation of thiols for the construction of S-S and S-N bonds and further applied the method in the sulfenylation of indoles. In continuation of our interest in the synthesis of organosulfur compounds, [31][32][33][34][35] we herein report a regio-and stereoselective three-component synthesis of novel (E)-1,3-diphenyl-1butene derivatives 7, that contain a sulfur atom, in the absence of a metal or a strong acid catalyst (Scheme 1b). In continuation of our interest in the synthesis of organosulfur compounds, [31][32][33][34][35] we herein report a regio-and stereoselective three-component synthesis of novel (E)-1,3-diphenyl-1butene derivatives 7, that contain a sulfur atom, in the absence of a metal or a strong acid catalyst (Scheme 1b).…”
mentioning
confidence: 99%
“…[22][23][24][25][26][27] We recently reported the diastereoselective synthesis of carbohydrate-based thiochroman derivatives 12 possessing antimalarial properties via a Lewis acid catalyzed intramolecular Friedel-Crafts alkylation of 2-C-branched phenylthiomethyl glucopyranosyl 8 as shown in Scheme 1 (b). [28][29][30][31][32][33] The analogy of the oxycarbonium intermediate 10 in Scheme 1 (b) to the oxycarbonium intermediate 5 in Scheme 1 (a), prompted us to synthesize a nitrogen analogue of the 2-C-branched phenylthiomethyl glucopyranosyl 8 and investigate if our established thiochroman synthesis methodology can be adopted to synthesize novel carbohydrate-based tetrahydropyranoquinolines in a diastereoselective fashion in addressing some of the limitations of the Povarov reaction.…”
mentioning
confidence: 99%